2016
DOI: 10.5114/wo.2016.61848
|View full text |Cite
|
Sign up to set email alerts
|

Impact of mTOR expression on clinical outcome in paediatric patients with B-cell acute lymphoblastic leukaemia – preliminary report

Abstract: Aim of the studyTo characterise expression of mTOR (mammalian target of rapamycin) in childhood B-cell acute lymphoblastic leukaemia (ALL), and to evaluate a possible link between mTOR and clinical characteristics.Material and methodsThe examined group consisted of 21 consecutive patients, aged 1–18 years, diagnosed with B-cell ALL in 2010, and 10 relapsed B-cell ALL patients diagnosed for the first time between 2009 and 2011, who developed relapse before 2014. All subjects were treated in the Department of Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Increased mTOR expression and/or activation are associated with poor outcomes in ALL [ 9 , 10 ]. Therapeutic effects of the mTOR inhibitor, rapamycin, have been tested in clinical trials [ 8 , 42 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased mTOR expression and/or activation are associated with poor outcomes in ALL [ 9 , 10 ]. Therapeutic effects of the mTOR inhibitor, rapamycin, have been tested in clinical trials [ 8 , 42 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…mTOR (mammalian Target of Rapamycin) is a serine/threonine kinase that directly regulates cellular proliferation and metabolism [ 7 , 8 ]. Increased expression and activation of mTOR are associated with poor outcomes in ALL [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“… [ 127 ] Leukemia Expression of mTOR and p-mTOR was associated higher risk of paediatric acute lymphoblastic leukaemia (ALL) relapse. [ 128 ] Expression of mTOR was upregulated in more than 50% of cases of ALL, both T- or B-ALL, and it was observed that the mean fold change of mTOR expression was higher in patients that did not respond to chemotherapy. [ 53 ] Multiple Myeloma Expression of mTOR or p-mTOR was observed in 25.8% FFPE samples from MM patients and high mTOR and p-mTOR were associated with male gender and older patients.…”
Section: Methodsmentioning
confidence: 99%
“…In the early 2010s, our and others' results confirmed that elevated mTOR activity is characteristic for human lymphoma and leukemia cells. Based on IHC and flow cytometry data, higher mTOR activity, especially in the presence of a high amount of mTORC2 complex, was correlated with worse prognosis and lower OS in lymphoma/leukemia patients [324][325][326][327].…”
Section: Characterization Of Mtor Hyperactivity and Its Correlation W...mentioning
confidence: 99%